Penerapan Fungsi Manajemen dalam Pelayanan Pastoral Bagi ODHIV (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to describe the application of management functions in pastoral care for PLHIV. The research method used is a descriptive qualitative method with data collection techniques through observation and interviews. The study was conducted at the HKBP AIDS Ministry (HAM) Balige. Research Findings indicate that the implementation of pastoral care management functions such as planning, organizing, implementing, monitoring and evaluation has been carried out well. The planning stage generally concerns the foundation's readiness to provide assistance in the form of data collection on the identity of the assisted, infrastructure, and scheduling. The organizing stage includes the division of personnel tasks, the formation of peer groups as service partners. The implementation stage is the aspect of implementing pastoral care with the aim of realizing assistance for PLHIV through early detection facilities, providing medication to PLHIV, and educating the community in the form of socialization or seminars. The monitoring stage is carried out by monitoring the progress of the assisted through ARV compliance forms. Meanwhile, evaluation of pastoral care for PLHIV is carried out in weekly meetings to ensure all activities are carried out properly. The implications of these findings support the principle of the importance of managerial aspects in pastoral care so that the assistance is more effective, structured and sustainable so that efforts to improve the quality of life and the healing process of PLHIV can be enhanced.